Analysis of the Psychological Barriers to Spoken English From Big Data and Cross-Cultural Perspectives - Mao, Wen (Frontiers in Psychology, 2022)
The goal of college English teaching is to cultivate students' comprehensive ability to use English. The study of oral English disorder is a hot issue in this subject. Based on the survey of non-English major college students' spoken language impairment, this paper analyzes the research status of spoken language impairment at home and abroad, and analyzes the theoretical basis of Swain's output hypothesis and Krashen's input hypothesis. With big data mining in colleges and universities as the entry point, the content, object and method of this paper are determined by combining qualitative and quantitative research with empirical research. Through the combination of classroom observation, questionnaire research, interview survey and other forms of research, it is concluded that the spoken language barriers of non-English major college students include language barriers and non-language barriers. The influencing factors of spoken language output disorder include subjective and objective aspects. The questionnaire content is analyzed from the three dimensions of students themselves, schools and education departments. In view of the existing problems, this paper proposes some ways to overcome the oral English barriers of non-English major college students, and suggests that non-English major college teachers should pay more attention to the cultural transmission of English-speaking countries in English classes, cultivate students' cross-cultural awareness and enhance students' enthusiasm in English learning, which is more conducive to overcoming the psychological barriers in oral English output.